Gastroduodenojejunal Invagination of Bleeding Gastric Schwannoma - Estrugo, Roberto; Matteucci, Pablo; Bowley, Roberto; Lapiedra, Eduardo (Cirugía del Uruguay, 1981)
A rare case of digestive hemorrhage due to invagina ted gastric schwannoma in first jejunal loop, in a pacient without prior gastric surgery, was operated with good postoperatory evolution.